The effects of pomegranate juice on monocrotaline-induced hypertensive pulmonary vascular changes and right ventricular hypertrophy in rats - aljanabi, mukhallad; Batainah, Hameed; Alzoubi, Abdallah; Rabab'h, Omar (Jordan Journal of Pharmaceutical Sciences, 2021)
Pulmonary hypertension is associated with structural pulmonary vascular changes. Due to the increase in pulmonary vascular resistance, right ventricular hypertrophy and right heart failure develop. Previous studies have shown that pomegranate juice has anti-inflammatory and anti-proliferative effects. The purpose of this study was to determine whether pomegranate juice intake could prevent or reverse changes in pulmonary circulation in a monocrotaline-induced pulmonary hypertension rat model. Pulmonary hypertension module was established in Westar rats by a single subcutaneous injection of monocrotaline (60mg/kg). Experimental groups were as follows: control, monocrotaline for 3 weeks, monocrotaline +Pomegranate juice for 3 weeks, and monocrotaline for 3 weeks followed by Pomegranate juice for 3 weeks (n=10 per group). The pathohistological changes of pulmonary arteries, right ventricular hypertrophy caused by monocrotaline, and pomegranate juice were analyzed. The thickness of the pulmonary arterioles and right ventricular are reduced significantly by the intake of pomegranate juice. Giving it with monocrotaline at day zero resulted in less thickening of pulmonary arterioles, alveolar septa, and right ventricle wall. We conclude that pomegranate juice intake ameliorates the pulmonary vascular remodeling developed in monocrotaline-induced pulmonary hypertension.